Adobe Flash 11 Stage3D (Molehill) game programming : beginner's guide : a step-by-step guide for creating stunning 3D games in Flash 11 Stage3D (Molehill) using AS3 and AGAL /: beginner's guide : a step-by-step guide for creating stunning 3D games in Flash 11 Stage3D (Molehill) using AS3 and AGAL. (2011) - Unknown
No abstract available